The Motivation for Code Switching in Written Context - Azam, Yasir (Pusat Pengajian Ilmu Kemanusiaan, 2019)
The act of alternating between different languages within a single discourse is not an unusual practice among multilingual speakers, and this act is commonly known as code-switching. (Gafaranga, 2007; Holmes & Wilson, 2017). In general, code switching is not confined only within the boundaries of oral communication, but they are regularly practiced in written communication as well (Sridhar, 1996; Montes-Alcala, 2015), for instance in blog writing. Blogs are basically personal journals, more often than not, written in a personal and informal manner on various kind of topics, and they are publically accessible online (Herring et al., 2004; Schmidt, 2007). This study is interested in understanding the motivation or the reason as to why writers alternate between two languages (in this case between Malay and English) in written blogs. Accordingly, this study anchors its analysis on the theoretical framework of Rational Choice theory (Myers-Scotton & Bolonyai, 2001). In this theory, language choices can be arranged along a continuum of markedness, and the choices are indexed with particular social roles associated with each language (Myers-Scotton, 1993; 2006).